2018
DOI: 10.1149/2.0241803jss
|View full text |Cite
|
Sign up to set email alerts
|

Research on R-Plane Sapphire Substrate CMP Removal Rate Based on a New-Type Alkaline Slurry

Abstract: Chemical mechanical polishing (CMP) is widely used as one of the most effective methods to achieve atomic-scale smooth surface. In order to investigate the mechanism of sapphire (α-Al 2 O 3 ) substrate CMP, the X-ray photo-emission spectroscopy (XPS) was applied to analyze the chemical state of elements. From XPS analysis it was demonstrated that AlO(OH) whose hardness was lower than α-Al 2 O 3 , existed only in c-plane sapphire after c-and r-plane polishing, so it's difficult to get high removal rate for r-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Under alkaline conditions, hydroxyl groups were dissociated to form surface functional groups with negative charges. They are existed compound of SiOK 23 as shown in Eq. 3:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under alkaline conditions, hydroxyl groups were dissociated to form surface functional groups with negative charges. They are existed compound of SiOK 23 as shown in Eq. 3:…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9 shows the particle size and zeta potential of silica particles when different potassium salts are added to the slurry. The concentration of the K + in the slurry is 0.14 M. By comparing the effects of four potassium salts on the particle size of silica, it can be seen that in the slurry added with KCl, the average particle size of silica is relatively large and the absolute value of zeta potential is relatively low, which increases the mechanical effect 23 of abrasive on LiTaO 3 wafer, so that LiTaO 3 wafer has a higher MRR.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, surfactants have an important impact on material removal rates and abrasive particle contamination of the polished surface during wafer polishing. [21][22][23] Park et al [24][25][26][27] investigated the effect of anionic surfactants such as polyacrylic acid (PAA), sodium dodecyl sulfate (SDS), dodecyl benzene sulfonate (DBSA), dodecyl phosphate (DP), and sodium lauroyl sarcosinate (SLS) on the polishing of Si 3 N 4 films and found that these anionic surfactants could be selectively adsorbed on the surface of Si 3 N 4 film through electrostatic action to form a dense adlayer. This adlayer prevented abrasive particles from approaching the film surface, thereby inhibiting the material removal rate of the Si 3 N 4 film.…”
mentioning
confidence: 99%
“…Sapphire has outstanding physical, chemical and optical characteristics so that it has been widely used in semiconductor devices, LEDs, solid-state lasers, infrared windows and precision optics. 1,2 In particular, sapphire can be applied as the substrate material for epitaxial growth of GaN, integrated circuits and other devices. [3][4][5][6] As a substrate material, the sapphire surface quality is greatly affecting the performance and reliability of semiconductor devices.…”
mentioning
confidence: 99%